Forecast cancer: the importance of biomimetic 3D in vitro models in cancer drug testing/discovery and therapy - Caballero, David (2022)
Nowadays, the pharmaceutical industry faces a significant challenge related to the high attrition rates of drugs, which is particularly astonishing in oncology [1]. Indeed, several studies have reported that about 95% of anti-cancer drugs tested in phase I fail to reach the market. The reasons for this decline may be very complex, but most likely, they are related to how potential drug candidates are tested, which is far from being optimal. Typically, drugs are evaluated using cancer cells seeded on conventionalâ flatâ tissue culture surfaces (e.g., Petri dishes, flasks, or multi-well plates), which cannot recapitulate the three-dimensional (3D) architecture, rich cellular content, and complex interactions of the native tumor microenvironment [2]. Under these oversimplistic conditions, cancer cells display extreme phenotypes and aberrant gene expression, producing a non-physiological response when exposed to drugs. Additionally, these conventional approaches cannot recapitulate many of the dynamic events occurring in the human body that are crucial in cancer dissemination, particularly fluid flow or gradient formation [3,Â 4]. Similarly, animal models (e.g., mice, pigs, or primates), besides being ethically controversial and expensive, do not mimic human physiology, particularly the immune system, which is critical during cancer progression and therapy response. Even though â humanizedâ mice have been reported to address this limitation, they are not available for the majority of research labs and are incompatible with high-throughput production, an imperative drug discovery/screening feature.